SVET, SKP and EIS study of the corrosion behaviour of high strength Al and Al-Li alloys used in aircraft fabrication - Moreto, J. A.; Marino, C. E. B.; Bose Filho, W. W.; Rocha, Luís Augusto Sousa Marques da [UNESP]; Fernandes, Jcs (Elsevier B.V., 2014)
The 2XXX and 7XXX series aluminium alloys are commonly used in aircraft applications where high strength-to-weight ratios are required. The present study aims to compare the corrosion resistance of two novel alloys developed for aircraft industry (AA2198-T851 and 7081-T73511) to that presented by the alternative base alloys (AA2524-T3 and 7050-T7451, respectively). Results indicate that AA2198-T851 may show a superior corrosion performance compared to AA2524-T3, being a potential candidate for its replacement, due to best mechanical properties. In what concerns the 7081-T73511, its resistance to pitting corrosion may be lower than for the base line alloy 7050-T7451. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Aluminium alloys; Intermetallics; EIS; SVET; SKP